2011
DOI: 10.2355/isijinternational.51.137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon and Manganese on the Quenching and Partitioning Response of CMnSi Steels

Abstract: Fig. 13. Situation of properties obtained in current research with respect to other proposed third generation AHSS development routes. 16) The data were collected from literature and corrected according to ISO 2566/1-1984(E) 34) to the ASTM E8 geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
96
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(105 citation statements)
references
References 19 publications
7
96
0
2
Order By: Relevance
“…For instance, tensile strength levels of 1500 MPa in combination with total elongation values in excess of 15% have been obtained in a 0?3C-3Mn-1?6Si (wt-%) alloy. 80 These property levels represent a special niche that is not readily achieved in low alloy steels processed by other methods, and unique property combinations can be obtained at even greater strength levels.…”
Section: Mechanical Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, tensile strength levels of 1500 MPa in combination with total elongation values in excess of 15% have been obtained in a 0?3C-3Mn-1?6Si (wt-%) alloy. 80 These property levels represent a special niche that is not readily achieved in low alloy steels processed by other methods, and unique property combinations can be obtained at even greater strength levels.…”
Section: Mechanical Behaviourmentioning
confidence: 99%
“…Increased manganese levels [80][81][82] have been shown to be effective at improving tensile properties in Q&P steels. For instance, tensile strength levels of 1500 MPa in combination with total elongation values in excess of 15% have been obtained in a 0?3C-3Mn-1?6Si (wt-%) alloy.…”
Section: Mechanical Behaviourmentioning
confidence: 99%
“…[1][2][3] The alloying concept of these steels relies on relatively high carbon content (up to 0.8 wt%) together with silicon and/or aluminum alloying.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that the Q&P processing of various AHSS enables the use of the TRIP effect to achieve a pronounced improvement of mechanical strength and ductility. [7][8][9] The Q&P processing consists of three stages: an initial quenching stage, a partitioning stage, and a final quenching stage. The austenitized steel is initially quenched to a temperature, T Q , in the M s À M f temperature range, and partially transformed to primary martensite.…”
mentioning
confidence: 99%